Augmented Reality Visualization–guided Microscopic Spine Surgery: Transvertebral Anterior Cervical Foraminotomy and Posterior Foraminotomy. (April 2018) - Umebayashi, Daisuke; Yamamoto, Yu; Nakajima, Yasuhiro; Fukaya, Nobuhisa; Hara, Masahito
Abstract : Objective: We describe intraoperative augmented reality (AR) imaging to obtain a microscopic view in spine keyhole surgery. Background: Minimally invasive keyhole surgery has been developed even for spine surgery, including transvertebral anterior cervical foraminotomy and posterior cervical laminoforaminotomy. These methods are complex and require a skillful technique. Therefore, inexperienced surgeons hesitate to perform keyhole surgeries. The technology used in surgery is rapidly advancing, including intraoperative imaging devices that have enabled AR imaging and facilitated complicated surgeries in many fields. However, data are not currently available on the use of AR imaging in spine surgery. The purpose of this article was to introduce the utility of AR for spine surgery. Methods: We performed O-arm intraoperative imaging to create an augmented imaging model in navigation systems. Navigation data were linked to a microscope to merge the live view and AR. Augmented reality imaging shows the model plan in the real-world surgical field. We used this novel method in patients who underwent both keyhole surgeries. Results: We successfully performed both surgeries using the AR visualization guide. Conclusions: The AR navigation system facilitates complicated keyhole surgeries in patients who undergo spine surgery. Study Design: Technical report